Insulinoma: A Comprehensive Summary of Two Cases - Pankaj Sharma; Sonia Sharma; Shivani Kalhan; Bhanu Pratap Singh; Sonam Sharma (Journal of Clinical and Diagnostic Research, 2014)
Pancreatic endocrine tumours are rare in occurrence. They may present with a baffling range of symptoms which pose a diagnostic dilemma. Two cases of pancreatic insulinoma are presented herewith. Both presented with neuro-psychiatric complaints and were treated symptomatically for depression, anxiety, seizures etc. The diagnosis in these patients was missed for years. Insulinoma being a great diagnostic challenge, requires reasonably high clinical suspicion, accurate biochemical diagnosis and radiological localization to avoid extensive surgery. The aim is to highlight the occurrence of this rare tumour at a tertiary care hospital.